Respuesta :
I don't like to eliminate this one
I will use subsitution
take 2nd equation and add 4+y to both sides
2x+4=y
sub 2x+4 for y in top equation
3x-5(2x+4)=15
3x-10x-20=15
-7x-20=15
add 20 to both sides
-7x=35
divide both sides by -7
x=-5
sub back
2x+4=y
2(-5)+4=y
-10+4=y
-6=y
x=-5
y=-6
(x,y)
(-5,-6)
A is answer
I will use subsitution
take 2nd equation and add 4+y to both sides
2x+4=y
sub 2x+4 for y in top equation
3x-5(2x+4)=15
3x-10x-20=15
-7x-20=15
add 20 to both sides
-7x=35
divide both sides by -7
x=-5
sub back
2x+4=y
2(-5)+4=y
-10+4=y
-6=y
x=-5
y=-6
(x,y)
(-5,-6)
A is answer
To solve this you would first multiply the second equation by -5 to get
3x - 5y = 15
-10x + 5y = 20
Then you add them both together to get
-7x=35
now divide each side by -7 to get
x=-5
Now we have our x we can look at the answers to see which one could be right. It looks like A has -5 as x so we can choose that one. If you want to find y also you can always plug in x into the first equation to figure it out. Hope this helped ^^
Answer=A
3x - 5y = 15
-10x + 5y = 20
Then you add them both together to get
-7x=35
now divide each side by -7 to get
x=-5
Now we have our x we can look at the answers to see which one could be right. It looks like A has -5 as x so we can choose that one. If you want to find y also you can always plug in x into the first equation to figure it out. Hope this helped ^^
Answer=A